Round table Theory and Method in Urban Ethnomusicology: June 3 – 5, 2011, Prague, Czech Republic. - Jurková, Zuzana (Lidé města, 2011)
Although urban studies are widely accepted in anthropology, ethnomusicology – even though it has been dedicated to urban topics for decades – lacks generally accepted theoretical discourse. This was the main reason for organizing the chamber round table “Theory and Method in Urban Ethnomusicology” June 3 – 5, 2011, at the Faculty of Humanities of Charles University in Prague. The round table thus became part of the long-term direction of the current ethnomusicological program for research in music in Prague.